Microscopy outperformed in a comparison of five methods for detecting Trichomonas vaginalis in symptomatic women. (March 2015) - Nathan, B; Appiah, J; Saunders, P; Heron, D; Nichols, T; Brum, R; Alexander, S; Baraitser, P; Ison, C
In the UK, despite its low sensitivity, wet mount microscopy is often the only method of detecting Trichomonas vaginalis infection. A study was conducted in symptomatic women to compare the performance of five methods for detecting T. vaginalis : an in-house polymerase chain reaction (PCR); Aptima T. vaginalis kit; OSOM ®Trichomonas Rapid Test; culture and microscopy. Symptomatic women underwent routine testing; microscopy and further swabs were taken for molecular testing, OSOM and culture. A true positive was defined as a sample that was positive for T. vaginalis by two or more different methods. Two hundred and forty-six women were recruited: 24 patients were positive for T. vaginalis by two or more different methods. Of these 24 patients, 21 patients were detected by real-time PCR (sensitivity 88%); 22 patients were detected by the Aptima T. vaginalis kit (sensitivity 92%); 22 patients were detected by OSOM (sensitivity 92%); nine were detected by wet mount microscopy (sensitivity 38%); and 21 were detected by culture (sensitivity 88%). Two patients were positive by just one method and were not considered true positives. All the other detection methods had a sensitivity to detect T. vaginalis that was significantly greater than wet mount microscopy, highlighting the number of cases that are routinely missed even in symptomatic women if microscopy is the only diagnostic method available.